Pemahaman Matan Hadith Mukhtalif (Studi Hadith Nabi Musa Memukul Wajah Malaikat Maut) - Purwantoro Purwantoro (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2018)
The content of the Prophet's Hadith will always be in line and in harmony with the content of the Qur'an. When encountering the Hadith content which is indicated as odd (mukhtalif), it is necessary to do in-depth research. It is found in the book of Saheeh Bukhari that the Prophet Musa struck the Angel of Death face. In simple words the hadith seems absurd, how a Prophet dared to hit the Angel face. In this study, we will find the fact that angels were human when they met the Prophets. When this human form, the Prophet Musa struck the face of the Angel of Death. Angels turned out to be a number of human beings when met with several Prophets.